Pengaruh Penerapan Konsep Perpajakan Modern terhadap Kepatuhan Wajib Pajak: Studi Pada KPP Pratama Gorontalo - Harun, Mutiya; Tuli, Hartati; Mahmud, Mulyani (VISA: Journal of Vision and Ideas, 2024)
Taxes are one of the largest types of state receipts and are used to finance government affairs, equalization of development, and social welfare of people. In order to increase tax revenue from taxpayers, the government has implemented a more modern taxation system that is expected to improve compliance by taxpayers, which include e-registration, e-VAT, and e-billing. The study was intended to find out how the application of the modern taxation system influences taxpayer compliance. In this study, the type of research used is a quantitative approach. The type of data used is primary data, that is, data obtained from the results of the questionnaire, and secondary data as supporting data. The results of the study showed that, firstly, variable X1 had no influence on variable Y. However, simultaneously, variables X1, X2 and X3 had a significant effect on the taxpayer compliance variable in KPP Pratama Gorontalo (Calculate more than Ftabel).